Pengaruh Independensi, Pengalaman, Due Professional Care Dan Akuntabilitas Terhadap Kualitas AuditStudi Empiris Terhadap Auditor KAP di Yogyakarta dan Jawa Tengah - Waskito, Bagas, Drs. Noer Sasongko, SE, Ak, M.Si (2016)
This study aims to identify, analyze and obtain empirical evidence about the influence of the independence , experience , due professional care and accountability to audit quality in auditor KAP in Yogyakarta and Central Java . This research was conducted using survey method with questionnaires . The study population was all auditors working on a Public Accounting Firm (KAP) and is listed in the Directory of Certified , in Yogyakarta and Central Java . Data analysis was performed to test the validity and reliability , test classic assumptions and hypothesis testing with multiple linear regression method . This study uses primary data and obtained by distributing questionnaires to 60 respondents . The results showed that the independence , experience and professional due care has no effect on audit quality , while accountability effect on audit quality .